1990
DOI: 10.1002/pros.2990160306
|View full text |Cite
|
Sign up to set email alerts
|

Non‐androgenic role of testis in enhancing ventral prostate growth in rats

Abstract: This study was conducted to investigate whether the testis, aside from its ability to secrete androgen, is able to promote prostatic growth in rats. Increasing quantities of silastic capsules filled with crystalline dihydrotestosterone (DHT) were implanted subcutaneously into adult Sprague-Dawley rats at the time of bilateral epididymo-orchiectomy or sham operation on the testes. Control animals received empty capsules. Twenty-eight days later, the growth of the ventral prostate as measured by wet weight, DNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Nevertheless, our study provides further evidence to suggest that prostate growth must depend on additional factors other than androgen, both because androgen levels are relatively low during this period of development, and because androgen replacement alone did not allow for the proper onset of PBP expression. Our study supports those which have demonstrated that there is a nonandrogenic role for the testis in prostate growth [40][41][42][43].…”
Section: Discussionsupporting
confidence: 95%
“…Nevertheless, our study provides further evidence to suggest that prostate growth must depend on additional factors other than androgen, both because androgen levels are relatively low during this period of development, and because androgen replacement alone did not allow for the proper onset of PBP expression. Our study supports those which have demonstrated that there is a nonandrogenic role for the testis in prostate growth [40][41][42][43].…”
Section: Discussionsupporting
confidence: 95%
“…To elucidate the interaction of the autonomic nervous system (ANS) and androgens in the growth of the rat prostate, we performed a unilateral ganglionectomy, but substituted supraphysiologic levels ofdihydrotestosterone (DHT) to promote maximal ventral prostate (VP) growth in an attempt to allow our surgical manipulations to have a greater effect [28]. As expected, the positive controls (no neural manipulation + DHT) showed marked hyperplasia of the ventral prostate (VP) (Fig.…”
Section: Supraphysiologic Dihydrotestosterone (Dht) and Denervationmentioning
confidence: 82%
“…One major advantage of this choice is that the induction of androgen-response genes is not affected by other factor(s) or hormone(s) secreted from the testis. In contrast, castration may cause gene expression changes that are regulated by nonandrogen testicular factor(s) (39,40). Furthermore, the induction of androgen-response genes in the prostate by hormone replacement should be more rapid than that by castration because the decay of androgen after castration takes time.…”
Section: Identification Of Genes That Are Up-or Down-regulated Bymentioning
confidence: 99%